Moral Stimuli in Developed Socialist Society - Sizonovas, Anatolijus (Problemos, 1981)
A classification and an essential interpretation of exclusively material, materialmoral, moral-material, purely moral stimuli are presented in the article. Basing on the data of sociological investigations, the types and forms of purely moral stimuli existing in a developed socialist society, are observed in detail by the author.